Criminal justice - Smartt, Ursula (SAGE course companions., 2006)
"This Course Companion in Criminal Justice by Ursula Smartt is to be applauded. It is an essential handbook for all students and practitioners who are studying the criminal justice system. The user-friendly framework provides students with practical support in how they can organise their approach to studying to maximise their knowledge and revision skills. I have no hesitation in commending this Companion as a valuable complementary text"--Professor Allyson MacVean, John Grieve Centre for Policing & Community Safety, Buckinghamshire Chilterns University College. Designed as an accessible refe